Exploring the Antimicrobial Potential of Azadirachta Indica Against Pseudomonas Aeruginosa a Natural Approach to Combat Drug Resistance - Hussain, Dilber; Hassan, Afaq; Rehman, Bushra; Shah, Mian Izaz Ali; Naeem, Muhammad; Raihan, Madeeha; Bukhari, Nain Taara; Faisal, Shah; Ullah, Iftikhar (Indus Journal of Bioscience Research, 2025)
Pseudomonas aeruginosa is a multidrug-resistant pathogen known for its ability to form biofilms, leading to chronic infections and reduced antibiotic effectiveness. Natural plant extracts, such as neem (Azadirachta indica), have shown promising antimicrobial properties. This study evaluates the antibacterial and anti-biofilm activities of neem extracts against P. aeruginosa. Phytochemical screening was conducted on ethanol and methanol extracts of neem to identify bioactive compounds. Antimicrobial susceptibility testing was performed using the agar well diffusion method, while the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined. Biofilm inhibition was assessed using the crystal violet assay at varying neem extract concentrations (50, 100, 250, and 500 µg/mL). Phytochemical analysis confirmed the presence of flavonoids, phenolic compounds, alkaloids, tannins, saponins, and terpenoids, with ethanol extracts showing higher concentrations. Neem extract exhibited dose-dependent antibacterial activity, with the highest inhibition zone of 22 mm at 500 µg/mL and an MIC of 100 µg/mL. The MBC was determined to be 250 µg/mL, confirming neem’s bactericidal properties. The biofilm inhibition assay showed that biofilm formation was reduced by 20% at 50 µg/mL and 85% at 500 µg/mL, indicating strong anti-adherence activity. Statistical analysis confirmed significant differences (p < 0.05) between different concentrations, with higher doses demonstrating stronger inhibition. Neem extract demonstrated potent antibacterial and anti-biofilm effects against Pseudomonas aeruginosa, with results comparable to some conventional antibiotics. The presence of bioactive compounds such as flavonoids and phenolic compounds contributes to its efficacy. Given the increasing challenge of antibiotic resistance, neem extract may serve as a potential natural antimicrobial agent or adjunct therapy.